Pragmatics of the Qur'an: Model Pemahaman Kisah Sayyidah Maryam yang Terikat Konteks - Fathurrosyid, Fathurrosyid (Lajnah Pentashihan Mushaf Al-Qur'an, 2016)
Textually, Maryam is a phenomenal public figure because her name becomes the name of the sura in the Qurâ€™an namely Sura Maryam. In addition to that, the story is rich with nuances of context, so it is interesting to study it by using the science of pragmatic approach that examines the relationship between the language unit of linguistic and non-linguistic context. This study is a library research using linguistic analysis and critical discourse. This study is significant not only because it justifies the position of the Qur'an that uses the nets device of the Arab localities, but at the same time, also forms the correction of the formal-structural reading which is oriented to the position of the subject, predicate and object, without negotiating the context. This study comes to the conclusion that the speech act of the fragmentation of the story of Maryam in SÅ«ra Ä€li Ê»ImrÄn/3: 36 has its locus to be informative sentence, while its illocus is in the form of assertive sentence whose meaning is to complain. As for the implicature shows the value of courtesy in speaking the word, while the implicature being labeled in the name of Maryam in SÅ«ra Ä€li Ê»ImrÄn/3: 42 is the resistance toward the accusation of pejorative status of Maryam as the